THE RELATIONSHIP BETWEEN ENTREPRENEURSHIP AND INNOVATION - Nabil Tarifi; Jomana Rawah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Entrepreneurship and innovation are gradually significant in all extents of business and management. Entrepreneurial start-ups stimulated the economy by classified new prospects and redirecting capitals. The reputable companies innovate to overcome or react to their competition as required abilities essential for the planning, development and launch of entrepreneurial and innovative projects. The study aimed to signify the relationship between entrepreneurship and innovation. The study used qualitative method in which various case studies were undertaken to compare different situations and understand the relationship between entrepreneurship and innovation. The data was collected by reviewed different articles from newspapers and magazines website to determine the relationship between entrepreneurship and innovation in Saudi Arabia had data collected up until 2017. The participation is entirely voluntarily and had option to withdraw the participation at any time. The data collected used the survey. The findings concluded that entrepreneurship and innovation were positively related and significant changes in the economy.